EFFECT OF HUMAN ACTIVIN-A ON IN-VITRO MATURATION OF oocYTES AND EARLY EMBRYONIC DEVELOPMENT IN BUFFALOES - SINGH, BEERENDRA; PRASAD, SHIV; GUPTA, H P; PRASAD, J K (The Indian Journal of Animal Reproduction, 2023)
The present study was designed to assess the effect of human Activin-A on in-vitro maturation of oocytesand early embryonic development. The oocytes were subjected to in-vitro maturation for 22 h in Medium-199supplemented with 10% serum, 0.5μg/ml FSH, 10 JU/ml LH, 1 μg/ml Estradiol-17a, 20ng/ml EGF and 50μMCysteam ine in four groups i.e. Group-I (without Activi n-A), Group-I I (Activin-A 5 ng/m I), Group-I II (Activin-A 10 ng/ml), Group-IV (Activin-A20 ng/ml) in CO2 incubator at 39°G temperature, 5% CO, and high humidity. The maturedoocytes were co-incubated with 1x106 sperms of buffalo in modified synthetic oviductal fluid (mSOF) mediumcontaining 1 0μg/ml heparin and after 22 h of sperm-oocyte incubation, fertilized oocytes were stripped off cumuluscells and cultured in mSOF medium for 7 days to study the embryonic development. A total of 665 oocytes weresubjected to in-vitro maturation in four groups 165, 167, 166 and 167, respectively in groups I, II, Ill and IV and 148(89.69%), 156 (93.41 %), 157 (94.57%) and 158 (94.61%) oocyles were matured, respectively in groups I, II, Ill andIV with overall maturation rate of 93.08%. The cleavage rates were 39.86%, 48.07%, 53.50%, and 59.49%,respectively with overall cleavage rate of 50.40%. It was significantly (P
Keywords: Buffalo; human activin-A; oocyles; in vitro maturation; in-vitro fertilization; in-vitro culture